A suboptimal array of options erodes the value of CAP ecological focus areas. (June 2019) - Nilsson, Lovisa; Clough, Yann; Smith, Henrik G.; Alkan Olsson, Johanna; Brady, Mark V.; Hristov, Jordan; Olsson, Peter; Skantze, Karin; Ståhlberg, David; Dänhardt, Juliana
Highlights: Limit agri-environmental measures to those with proven biodiversity benefits. Incentives needed for optimizing placement of agri-environmental measures. CAP greening experienced as complicated and without environmental benefits. Abstract: As a part of the greening of the EU's Common Agricultural Policy in 2013, Ecological Focus Areas (EFA) became mandatory for many European farmers, with the aim to enhance on-farm biodiversity. However, their effects on biodiversity have been disputed. In this interdisciplinary effort, we assessed the effects of current and alternative formulations of EFA regulations in Sweden. By complementing economic and ecological modelling with interviews with persons at administrative and advisory bodies and a narrative decision game with farmers, we were able to demonstrate key shortcomings of mandatory EFAs as a policy instrument. In particular, we evaluated if requirements to increase the quality of EFAs and regulations allowing their collective implementation, have the potential to increase their effectiveness in benefitting functional biodiversity. We focused on how biodiversity underpinning crop pollination and natural pest control would be affected by alternative regulations. First, we show that several of the possible EFA measures have no or minimal actual effect on biodiversity. Second, we demonstrate the need for appropriate incentives for farmers to choose and place agri-environmental measures in an environmentally desirable way. The EFA regulation is experienced as complicated and without any clear environmental benefits for the participants in this study. As a result, the confidence in the policy is undermined. Third, we demonstrate the challenge of devising compulsory measures to improve biodiversity that also need to fulfil demands on being flexible and easy to administrate. Our results indicate that the latter goal has taken precedence over the former, and thus providing an explanation of the poor design of the EFA regulation from a biodiversity perspective. We argue that to enhance biodiversity in farmland through general agri-environmental measures, only measures with clear benefits for biodiversity can be on the menu. Further, better information as well as incentives for optimizing EFA placement for biodiversity on farms are needed and combined with stricter rules on quality and placement where appropriate.